Limites e potencialidades das práticas ambientais do Instituto Australis – Imbituba/SC: uma análise à luz de fundamentos da educação ambiental crítico-transformadora via temas geradores - Antunes, Débora Damianus (Universidade Federal de São Carlos, 2023)
The aim of this paper is to critically analyze the environmental education activities carried out by the Australis Institute in Imbituba/SC during "Whale Month", which celebrates the month with the highest number of right whales (Eubalaena australis) on the southern coast of Santa Catarina. This analysis sought to identify the limits and potential of the educational practices carried out by the Australis Institute team during this month, in 2021, adopting the concepts of dialogue, problematization, contextualization and interdisciplinarity conceived within the framework of the foundations of Critical-Transformative Environmental Education via generating themes as an analytical framework. The results of the analysis reinforce the importance of carrying out activities that address environmental problems, aim to increase visitors' criticality and lead them to critically reflect on the issues addressed, so that they become more aware and can once again feel part of nature, and the analysis also points to new forms of educational approach during the application of the activities developed, using interdisciplinarity as a key point.
Limits and potentialities of the Institute's environmental practices Australis – Imbituba/SC: an analysis in the light of the fundamentals of the critical-transformative environmental education via themes Generators
Keywords: Interdisciplinaridade; Criticidade; Baleia-franca-austral; Mês da Baleia-franca; Espécie Ameaçada; Interdisciplinarity; Criticality; Southern Right Whale; Right Whale Month; Threatened Species; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO